Internationell rörlighet inom den högre utbildningen : Studentutbytet mellan norra Sverige och östra Europa - Sundquist, Elin (2013)
As a result of the internationalization of higher education, students around the world choose study abroad. This essay examines the mobility of students between Eastern Europe and Northern Sweden to gain an understanding of the objective of their stay in Sweden and which ambitions they have. There is also a subsidiary aim to find out whether differences exist between women and men come to study abroad. The approach of this has taken place primarily through interviews with selected respondents. The paper was commissioned by Professor Ulf Mellström who is responsible for the project "Globalized eduscapes; student, learning and mobility in knowledge society" (funded by the Swedish Research Council 2010-2013) whose main purpose is to examine international students' situation in Sweden. This essay should be considered as a sub-project within the Globalized eduscapes project.The main result of the interviews is that many of the students that participated in this study choose to study abroad, in Sweden, because of the poor quality of educations in their home country where the education system is, according to them, part of a corruption scheme and therefore unreliable. The Swedish education system has a solid reputation and has attracted many to study here. In some cases, the Luleå University of Technology (LTU) recruited exchange students in order to maintain a certain program that would otherwise have been threatened with closure. The number of exchange students has decreased because scholarship opportunities have decreased and thus they cannot afford to live here, even though the studies are free. Master students have also been reduced with the introduction of tuition fees in 2011.The home countries of the respondents’ are characterizes by a strong educational tradition. It is not enough with one degree; you need to have at least two. Their parents offer financial help and inspire them to become successful. The female students are drawn abroad to study, not only for studies sake, but also to get away from traditional ...